Aproximação entre civis e militares com a criação do Ministério da Defesa - Vasconcellos, Carlos Antonio Raposo de (2011)
The objective of this thesis is to verify the level of relationship between civilian and military people, before and after the creation of the Ministry of Defense, in 1999. Initially there are descriptions about the arising of each Armed Force and it is verified that the Brazilian Navy and Army, were created in 1820s because of need of security and defense that was necessary to the country but were obtained by its own people´s initiative and will. The Air Force, in the 1940s, was originated from the junction of the aeronautics segments of the Navy and Army. It is observed that the society does not get involved, as they should, in terms of security and National Defense, not even during and after the period under Military Governments. It is noted that this apathy, reaction of the society towards the theme, has several reasons. There is lack of information about this topic. Twenty years under Military Governments have passed, and the wound is difficult to be healed and the desired proximity between civilian and military groups is an issue to be studied. After the creation of the Ministry of Defense, it was noted that, in some way, civilians and military people were approached. Including exchange of knowledge. There were conferences, symposiums and meetings about Defense issues and high-level documents were studied and elaborated by civilian and military people. The National Security Strategy revisions, the National Defense Strategy elaboration and White Paper preparation studies are examples that confirm this approach. Before the existence of the Ministry of Defense such a fact did not occur. The present study has the objective to evaluate the creation of the Ministry of Defense as a possible inflexion point in the participation of society in the subjects of Defense and the approach between civilian and military people.